Care and Covenant : A Jewish Bioethic of Responsibility - Weiner, Jason (Book collections on Project MUSE., 2022)
"The Jewish tradition has important perspectives, history and wisdom that can contribute significantly to crucial contemporary healthcare deliberations. This book is an attempt to show how numerous classic Jewish texts and ideas have significant things to say about some of the most urgent debates in the world of medicine today, with the potential to significantly expand and benefit the field of bioethics. But this book is not only about applying classical Jewish values to bioethical dilemmas. It seeks to develop an approach that is primarily informed by personal and communal obligations and social responsibilities. Jewish values focus on requirements, obligations, and commandments, and has thus sometimes been called an "Ethics of Responsibility," by advancing new relevant approaches that can encourage healthcare providers to remain dedicated to preventing harm and providing compassionate care to all, based on these inspiring and timeless values. Each chapter of this book explores questions such as: "Are we expected to risk our lives on behalf of others?" "When we can only help a limited number of people, how do we prioritize?" "What are the obligations and expectations of a society or government?" "Are issues of cultural sensitivity relevant in how we discharge our obligations to others?" "What should we do when obligations for others violate our own moral principles or commitments?" "Are there limits to how far one can be expected to go for others?" These and other issues are addressed in this book, as it attempts to describe a meaningful and compassionate Jewish bioethic of responsibility for our times"--